Digital technological innovation and urban carbon emission intensity: a nonlinear path toward sustainability - Xu, Shujing; Li, Jiapeng; Ya, Ji; Li, Han; Xia, Donglai; Zhang, Song (Frontiers in Environmental Science, 2025)
With the advancement of sustainable development goals, digital technological innovation has emerged as a critical pathway for mitigating urban carbon emission intensity. Using balanced panel data from 282 Chinese cities spanning 2012-2019, this study employs fixed-effect models and mediating effect analysi to investigate the nonlinear impact of digital technology innovation on urban carbon intensity. The findings reveal the following. (1) There exists an inverted U-shaped relationship between digital technological innovation and carbon intensity. (2) A nonlinear mediation mechanism is identified, whereby digital technological innovation influences carbon intensity through its effects on energy intensity and governmental environmental attention. (3) Substantive digital technological innovation reaches the turning point more rapidly. (4) The inverted U-shaped relationship holds exclusively for non-key environmental protection cities, while it is not evident in key environmental protection cities. (5) This relationship is consistently observed across both Broadband China pilot cities and non-pilot cities, suggesting that the findings are robust and applicable to different types of cities. These findings not only deepen our understanding of the complex interplay between digital technological innovation and carbon intensity but also provide valuable theoretical insights and practical guidance for achieving sustainable development objectives.